Grammatical Statements Specific to Vocative Case From Normative Rules to a Pragmatic Perspective - zehar, mohammed (El Omda in Linguistics and Discourse Analysis, 2025)
according to solid controls during The accomplishment of the speech act. This is what the research paper will attempt to clarify through a descriptive reading of the various statements of grammarians from a pragmatic perspective and a feature that enshrines the principle of intentionality in contemporary pragmatics.